Forensic Data Analysis on Smartphone Memory Android Operating System Using Framework GRR - Arman Syah Putra; Muji Santoso; I Iwan; M Mudrika; Bambang Harianto; Popon Handayani (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2022)
The background of this research is how to find out and search for hidden data that has been deleted on a hidden smartphone device so that it can be used as evidence of the crime, especially in cybercrimes. The method used in this study uses the four-step method, namely, the first stage is collecting data, the second stage is looking for data, the third stage is analyzing data and the fourth stage is reporting the existence of these four stages, the method will be able to help research. The problem raised in this research is how to find evidence on a smartphone that was deleted by the users of, the crime so that the data can be returned and can make evidence as evidence of a crime. The purpose of this study is to find evidence on a smartphone and test whether the data is really the data you are looking for so that it can be used as evidence in cybercrimes.